Sclerosing nevus with pseudomelanomatous features: dermoscopic and confocal aspects. (9th November 2018) - Bombonato, C.; Pampena, R.; Franceschini, C.; Piana, S.; Perino, F.; Di Stefani, A.; Ardigò, M.; Fargnoli, M.C.; Frascione, P.; Borsari, S.; Pellacani, G.; Peris, K.; et al.
Abstract: Background: Sclerosing nevus with pseudomelanomatous features (SNPFs) is a clinical and pathologic entity that mimics melanoma both clinically and histologically. The lesion is a melanocytic nevus, histologically characterized by fibrosis and a pseudomelanomatous proliferation. It is typically seen in young to middle‐aged individuals, mainly on the back, where microtrauma or inflammatory changes are more frequent. Dermoscopic description of SNPF has been reported so far in one case series. Objective: The aim of our study was to describe the dermoscopic and confocal features of SNPF. Methods: Histopathologically confirmed cases of SNPF were retrospectively collected from three referral centres in Italy. Only lesions with available clinical, dermoscopic and histopathological data were included; confocal images were also retrieved, when available. Lesions were evaluated for the presence of 12 dermoscopic and five confocal criteria previously described. Results: The study population included 93 lesions in as many patients (71 men and 22 women; median age: 38 years). Dermoscopically, we found a predominance of dark colours, in particular brown and blue, which were found in all lesions and the vast majority of the lesions (86/93; 92.5%) displayed at least one structureless area. By the combination of colours and structures, we observed that the majority of the lesions (67/92; 72%) were characterized by more than one structure and more than one colour. Confocal evaluation was performed on a subset of 24/93 lesions showing a regular architecture pattern (19/24 cases, 79%), with a predominance of the ringed pattern. The presence of focal cytologic atypia at the dermal‐epidermal junction was present in 12/24 cases (50%) with a prevalent dendritic‐shaped cell proliferation. Conclusions: The current study demonstrated that SNPF was frequently characterized, on dermoscopic examination, by more than one structure and more than one colour and on confocal microscopy by a regular ringed pattern with focal dendritic atypical cells.